Micro-Spherical Sulfur/Graphene Oxide Composite via Spray Drying for High Performance Lithium Sulfur Batteries - Tian, Yuan; Sun, Zhenghao; Zhang, Yongguang; Wang, Xin; Bakenov, Zhumabay; Yin, Fuxing (Nanomaterials, 2018)
An efficient, industry-accepted spray drying method was used to synthesize microspherical sulfur/graphene oxide (S/GO) composites as cathode materials within lithium sulfur batteries. The as-designed wrapping of the sulfur-nanoparticles, with wrinkled GO composites, was characterized by scanning electron microscopy (SEM) and transmission electron microscopy (TEM). The unique morphological design of this material enabled superior discharge capacity and cycling performance, demonstrating a high initial discharge capacity of 1400 mAh g􀀀1 at 0.1 C. The discharge capacity remained at 828 mAh g􀀀1 after 150 cycles. The superior electrochemical performance indicates that the S/GO composite improves electrical conductivity and alleviates the shuttle effect. This study represents the first time such a facile spray drying method has been adopted for lithium sulfur batteries and used in the fabrication of S/GO composites
Keywords: sulfur; graphene oxide (S/GO) composites; lithium sulfur batteries; spray drying